2015
DOI: 10.1021/jacs.5b03803
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Nature of Interaction between Graphene Oxide and Lipid Membrane by Surface-Enhanced Infrared Absorption Spectroscopy

Abstract: Revealing the nature of interaction between graphene oxide (GO) and lipid membrane is a crucial issue but still remains challenging. Here, we describe our recent effort toward this direction by studying the GO-induced vibrational changes of interfacial water and lipid membrane with surface-enhanced infrared absorption (SEIRA) spectroscopy. The experimental results provide evidence that overcoming the electrostatic repulsion of phosphate group, its hydrogen bonding attraction as well as the electrostatic and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 40 publications
(29 reference statements)
4
83
0
Order By: Relevance
“…Based on these observations, we summarized our findings in Figure 1C, D. Previous studies indicated that water mediates the hydrogen bonding interaction between DOPC liposomes and GO, 20 and thus the interface between these two is not fully dehydrated. In addition, DOPC and GO interact mainly on the edge of GO, which is more hydrophilic than the carbon-rich domains in the interior.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Based on these observations, we summarized our findings in Figure 1C, D. Previous studies indicated that water mediates the hydrogen bonding interaction between DOPC liposomes and GO, 20 and thus the interface between these two is not fully dehydrated. In addition, DOPC and GO interact mainly on the edge of GO, which is more hydrophilic than the carbon-rich domains in the interior.…”
Section: Resultssupporting
confidence: 61%
“…In the case of DOPC adsorption, water release is not a main factor, and their hydrogen bonding interaction is believed to be mediated by a water molecule. 20 It is the removal of extra salt ions that consumed the enthalpy.…”
Section: Resultsmentioning
confidence: 99%
“…At least four kinds of interactive forces exist: electrostatic attraction, electrostatic repulsion, hydrogen bonding, and hydrophobic interaction (Wu et al 2015). It is well known that a GO membrane can be strengthened by crosslinking with divalent metal ions (Park et al 2008).…”
Section: Stability Of Go Membranes In DI Watermentioning
confidence: 99%
“…For example, several groups have demonstrated that graphene oxide (GO) and reduced GO (rGO) nanosheets exerted hemolysis effects on red blood cells (RBCs) . This hemolytic toxicity is suggested to be related to the destructive effect of Gr nanosheets on cell membranes . These studies indicated the underlying molecular mechanism for this cell membrane destruction is due to the strong dispersion interactions between Gr and lipid molecules—Gr and its derivatives cannot only insert/penetrate into the cell membrane, but also extract large amounts of phospholipids molecules directly from the cell membrane, thus eventually cause membrane stress and degradation.…”
Section: Introductionmentioning
confidence: 99%